Altered structural and functional connectivity of the insula in functional dyspepsia. Issue 9 (23rd April 2018) - Liu, P.; Fan, Y.; Wei, Y.; Zeng, F.; Li, R.; Fei, N.; Qin, W.
Abstract: Background: Functional dyspepsia (FD) is a common functional gastrointestinal disease. Neuroimaging studies have identified that insula is involved in the pathogenesis of FD. However, less is known about structural and functional connectivity of insula in FD. Methods: In this study, 67 FD patients and 46 healthy controls (HCs) underwent structural MRI, resting‐state functional MRI, diffusion tensor imaging (DTI) scans, and clinical assessment. We used the 3 neuroimaging modalities to investigate structural and functional connectivity of insula between FD patients and HCs, and we examined relationships between the neuroimaging findings and clinical symptoms. Key Results: Compared with HCs, (i) FD patients had decreased gray matter density in right insula according to voxel‐based morphometry method, which region was targeted as region of interest for further analysis of structural and functional connectivity; (ii) FD patients had lower connection probability in right anterior insula with right thalamus, right internal capsule (IC), and right external capsule (EC); (iii) FD patients had decreased functional connectivity of the right anterior insula with right thalamus and right pregenual anterior cingulate cortex (pACC); and (iv) FD patients had negative correlation between disease duration and the functional connectivity of right anterior insula with thalamus. Conclusions and Inferences: The present findings reveal that alterations of structural and/or functional connectivity of right anterior insula with regions, including thalamus, IC, EC, and pACC, may be mainly implicated in abnormalities of visceral sensory processing and related affective responses in FD patients. Finally, this study could enhance understanding of the pathophysiology of FD. Abstract : Functional dyspepsia is a highly prevalent functional gastrointestinal disease. In this study, we recruited 67 FD patients and 46 healthy controls and employed their neuroimaging modalities including structural MRI, resting‐state functional MRI, diffusion tensor imaging to investigate structural and functional connectivity of insula. The present findings reveal that alterations of structural and/or functional connectivity of the right anterior insula with the regions, including the thalamus, internal capsule, external capsule, and pregenual anterior cingulate cortex, may be mainly implicated in abnormalities of visceral sensory processing, primary taste input transition, and related affective responses in FD patients.